Risk assessment of Kuala Lumpur municipal landfills - Delphi Approach - Theng, Lee Chong (2000)
Most of the sol id waste disposal sites in Malaysia are either open dumps or controlled tipping. The risks from these sites are expected to be high especially the contamination of soil, air, surface and underground water, and also the i mp acts on flora and fauna. All these impacts have direct and indirect links to human being. The risks associated with solid waste disposal sites involved three compartments or media, i.e. the atmosphere, water and soil. This 'Cross media' or 'Multimedia' impacts phenomenon has made risk assessment of landfill site as a complicated process. This study discusses the development of a simple risk assessment systems for landfill sites by using the Delphi Approach, which emphasises the development of weight age for different parameters selected in the risk assessment procedures. The environmental conditions and risks of all closed and active disposal sites in Kuala Lumpur are assessed based on nine criteria representing the multi-media components of the environment, i.e. water quality, social , gas emissions, landuse, hydrology, geology, ecotoxicology, plant ecology and chemical constituents in soil and groundwater. These criteria have gathered 59 parameters and each parameter was assigned a weightage of importance which was then assessed with the actual situation of the landfill sites. The final scores can be aggregated according to individual criteria or across the multi-criteria for the overall environmental conditions. The results of assessments indicated that most of the solid waste disposal sites in the study area showed significant level of risks especially the still active site, i.e. Taman Beringin landfill site. This study also presents the evaluations of the pollution levels of all the disposal sites in terms of water and soil contamination by selected chemicals, and also air pollution by selected gases emitted from the sites. Landfill Pollution Index (LPI) was also developed in this study and were calculated for each disposal site i n the study area. The results show that Taman Beringin was the most polluted landfill with the LPI of 719.5576, followed by Jinjang Utara (383.5085), Paka 1 (197.6589), Brickfields (128.8949), Paka 2 (113.7235), Sri Petaling (30.8083) and Sungei Besi (17.8656). In summary, new evaluation systems had been introduced in this study in order to produce simple and reliable tools to evaluate or assess the pollution and risk levels for municipal waste landfill sites in Malaysia. B sed on the assessment of Kuala Lumpur landfill sites, it can be concluded that the risk and pollution levels of landfill sites in Kuala Lumpur area are relatively high, but it is site-specific and various from one landfill site to another.